Analysis of Robert Entman's Framing in The Netflix's Documentary Film “Ice Cold: Murder, Coffee, and Jessica Wongso” - Basarah, Finy Fitrya; Ridaryanthi, Melly; Winarty, Shenthya (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2025)
Jessica Kumala Wongso suddenly became a “celebrity” because of the murder case she was accused of in 2016. In 2023, after more than 5 years since the case was decided by the court, the Netflix reconstruct this case in a documentary film “Ice Cold: Murder, Coffee, and Jessica Wongso”. This research wants to see the media construction by using Robert Entman's framing analysis model, which have some categorizations: Issue Selection and Highlighting of Certain Aspects of the Issue, Define Problems, Diagnose Causes, Make Moral Judgment and Treatment Recommendations. The results show that the media constructs messages by taking opinions and statements from various sources; before, during, and after the trial process ends. This documentary does not side with or against Mirna or Jessica, but rather highlights how the criminal justice system in Indonesia actually works. This film highlights what the criminal justice system, really is in Indonesia. The victim here is not only Mirna (if there is a case), but also Jessica as a victim of injustice in the criminal justice system in Indonesia, and the Indonesian people because the public in general has the right to know how the situation actually happened. When connected to the Sustainable Development Goals, it can be seen that one of element at number 16, Justice, is still a concern, especially in Indonesia